Sex-specific effects of different types of prenatal stress on foetal testosterone levels and NMDA expression in mice - Kalinichenko, Liubov; Smaga, Irena; Filip, Malgorzata; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (Behavioural brain research, 2023)
Prenatal stress is a critical life event often resulting in mental illnesses in the offspring. The critical developmental processes, which might trigger a cascade of molecular events resulting in mental disorders in adulthood, are still to be elucidated. Here we proposed that sex hormones, particularly testosterone, might determine the “developmental programming” of long-term consequences of prenatal stress in foetuses of both sexes. We observed that severe prenatal stress in the model of repeated corticosterone injections enhanced brain levels of corticosterone and testosterone in male foetuses. The expression of GluN1 and GluN2A, but not GluN2B NMDA receptor subunits were significantly reduced in the brain of stressed male foetuses. However, female foetuses were protected against stress effects on the brain corticosterone and testosterone levels. More moderate types of stress, such as repeated restraint stress and chronic unpredictable stress, did not induce an increase in brain corticosterone in dams and testosterone concentrations in foetuses of both sexes. Moreover, chronic unpredictable stress reduced brain testosterone concentration in male foetuses. Altogether, changes in brain testosterone level might be one of the crucial mechanisms determining the development of long-term consequences of severe prenatal stress in male, but not in female foetuses. Targeting this mechanism might allow to develop principally new prediction and therapeutic approaches for prenatal stress-associated psychiatric disorders.
Online verfügbar 23 November 2022, Artikelversion 1 December 2022
Gesehen am 15.05.2023